Analisis Pendekatan Mimetik dalam Menggali Makna Puisi “Merayakan Kehilangan” Karya Ulfiyanti Nawangsih Rahayu - Desta Aldi Pratama; Dian Ayu Puspita Sari; Eka Wening Safitri; Faiza Najma Khoirunissa; Maulida Alfi Sa’adah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
A literary work is a work that not only has beauty, but also has meaning in it. Poetry is an imaginative work with words that contain aesthetics and simplicity, but is difficult to understand for readers who have little knowledge in analyzing poetry. Someone who likes to write uses poetry as motivation. The author is interested in analyzing the poem